Ibrutinib impairs IGF-1-dependent activation of intracellular Ca handling in isolated mouse ventricular myocytes - Tarnowski, Daniel; Feder, Anna-Lena; Trum, Maximilian; Kreitmeier, Klaus-Georg; Stengel, Laura; Maier, Lars S.; Sag, Can Martin (Frontiers in Cardiovascular Medicine, 2023)
Background The Bruton tyrosine kinase (BTK) inhibitor Ibrutinib is associated with a higher incidence of cardiotoxic side effects including heart failure (HF). Objectives Ibrutinib is capable of inhibiting PI3K/Akt signaling in neonatal rat ventricular cardiomyocytes when stimulated with insulin-like growth factor 1 (IGF-1). We therefore hypothesized that Ibrutinib might disrupt IGF-1-mediated activation of intracellular Ca handling in adult mouse cardiomyocytes by inhibiting PI3K/Akt signaling. Methods Isolated ventricular myocytes (C57BL6/J) were exposed to IGF-1 at 10 nmol/L in the presence or absence of Ibrutinib (1 µmol/L) or Acalabrutinib (10 µmol/L; cell culture for 24 ± 2 h). Intracellular Ca handling was measured by epifluorescence (Fura-2 AM) and confocal microscopy (Fluo-4 AM). Ruptured-patch whole-cell voltage-clamp was used to measure ICa. Levels of key cardiac Ca handling proteins were investigated by immunoblots. Results IGF-1 significantly increased Ca transient amplitudes by ∼83% as compared to vehicle treated control cells. This was associated with unaffected diastolic Ca, enhanced SR Ca loading and increased ICa. Co-treatment with Ibrutinib attenuated both the IGF-1-mediated increase in SR Ca content and in ICa. IGF-1 treated cardiomyocytes had significantly increased levels of pS473Akt/Akt and SERCA2a expression as compared to cells concomitantly treated with IGF-1 and Ibrutinib. SR Ca release (as assessed by Ca spark frequency) was unaffected by either treatment. In order to test for potential off-target effects, second generation BTK inhibitor Acalabrutinib with greater BTK selectivity and lower cardiovascular toxicity was tested for IGF1-mediated activation of intracellular Ca handling. Acalabrutinib induced similar effects on Ca handling in IGF-1 treated cultured myocytes as Ibrutinib in regard to decreased Ca transient amplitude and slowed Ca transient decay, hence implying a functional class effect of BTK inhibitors in cardiac myocytes. Conclusions Inhibition of BTK by Ibrutinib impairs IGF-1-dependent activation of intracellular Ca handling in adult ventricular mouse myocytes in the face of disrupted Akt signaling and absent SERCA2a upregulation.